Seasonal rhythm of development of species Tilia L. in the arboretum of Khakasia - G. N. Gordeeva (Проблемы ботаники Южной Сибири и Монголии, 2019)
This article provides the analyses of the growth and the development of eight species Tilia L., which aregrown in the arboretum of Khakasia and which are of different origin. The period and time of plant flowering, rhythm oftheir development, vegetation periods as well as the peculiarities of linden responses under the dry conditions of steppezone of the Republic were determined. It was found out that small and average values of variation coefficient for thedates of the major phases in the plant development prove the permanence for the growth of particular species of linden.Using commonly known methods of phonological observations of woody plants, statistics for the last 10 years, takinginto account seven indicators, rather promising (75,0 %), promising (12,5 %) species of linden were distinguished for treeplanting in the residential areas of Khakasia and the south of Krasnoyarsk Krai.